2014
DOI: 10.1007/s40615-014-0006-6
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Programs May Have Beneficial or Adverse Effects on Fat Mass and Insulin Sensitivity in Overweight and Obese Black Women

Abstract: ObjectiveWeight loss interventions have produced little change in insulin sensitivity in black women, but mean data may obscure metabolic benefit to some and adverse effects for others. Accordingly, we analyzed insulin sensitivity relative to fat mass change following a weight loss program.Design and MethodsFifty-four black women (BMI range 25.9 to 54.7 kg/m2) completed the 6-month program that included nutrition information and worksite exercise facilities. Fat mass was measured by dual-energy X-ray absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…There are public health implications for the results of this study (Leon et al, 2014; Assari et al, 2015a; Krishna et al, 2015). Although, Black men and women with sustained high BMI do not report high depressive symptoms, there should still exist efforts to reduce the sustained high levels of BMI among Black men and women, similar to Whites.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…There are public health implications for the results of this study (Leon et al, 2014; Assari et al, 2015a; Krishna et al, 2015). Although, Black men and women with sustained high BMI do not report high depressive symptoms, there should still exist efforts to reduce the sustained high levels of BMI among Black men and women, similar to Whites.…”
Section: Discussionmentioning
confidence: 81%
“…To maximize benefits, interventions and programs may be tailored to race and gender to match that of the target population. One study that implemented a weight loss intervention among Black women reported that those with the greatest fat mass loss improved insulin sensitivity while those with fat mass gain, which was common, had reduced insulin sensitivity following the 6-month program (Leon et al, 2014). These results demonstrate that additional support may be beneficial for Black women in weight loss programs who fail to achieve optimal weight loss goals.…”
Section: Discussionmentioning
confidence: 99%
“…These results may have clinical and public health implications. Social groups have differences in patterns of comorbidity of health problems [149,150,151]. At least for Whites, this study highlights the need for a multidisciplinary and team approach to reduce the burden of obesity and depression.…”
Section: Discussionmentioning
confidence: 99%